Exploring the Role of Social Capital, Managerial Skills, and Technological Literacy in Shaping Entrepreneurial Interest through Entrepreneurial Motivation - Isma, Andika; Hajar Dewantara; Andi Naila Quin Azisah Alisyahbana; Salim Diarra; Soussou Raharimalala (PT Mattawang Mediatama Solution, 2024)
Unemployment is a major issue in Indonesia. This occurs because Indonesia is a country with a relatively high population growth rate, which affects the competition for job opportunities. One of the strategies considered effective in addressing unemployment is to create or increase the number of entrepreneurs. This study aims to determine the direct and indirect effects of social capital, managerial skills, technology literacy, and entrepreneurial motivation on entrepreneurial interest. The sampling technique used is Proportional Random Sampling, with a total of 100 students from the Faculty of Economics and Business Universitas Negeri Makassar. The results indicate that both directly and indirectly, social capital, managerial skills, technology literacy, and entrepreneurial motivation significantly influence entrepreneurial interest. Based on the findings of this study, it can serve as a source of information or a reference for educators or lecturers to guide and assist students in developing entrepreneurial skills. Students are encouraged to deepen their skills related to business management, not only focusing on the products produced but also being capable of conducting marketing activities and making decisions regarding business evaluation with the aim of developing their businesses. Furthermore, future researchers are encouraged to deepen and expand this research in terms of variables and research method development.